2019
DOI: 10.2478/hukin-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Changes at the End of the Soccer Season in Elite Female Athletes

Abstract: This study compares and describes relationships among stress-recovery indices, the heart rate variability index, and the Cooper and Yo-Yo IR1 tests among female soccer players during the last six weeks of the competitive season. Sixteen female soccer players engaged in a pre-test of all of the variables. After having their training monitored for six weeks, a post-test was administered. The results revealed significant (p < 0.05) differences in the specific stress-recovery scales of the RESTQ-sport and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Bellenger et al [21], in a recent systematic review with meta-analysis, highlighted the need to use monitoring systems that accurately reflect the athletes' adaptations to the training stimulus. Although there have been numerous research studies using the HRV measure to check wellness and training adaptation in athletes [22,23], these have not focused on performance improvement based on HRV-guided training but have followed training interventions based on a traditional and nonindividualized methodology.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Bellenger et al [21], in a recent systematic review with meta-analysis, highlighted the need to use monitoring systems that accurately reflect the athletes' adaptations to the training stimulus. Although there have been numerous research studies using the HRV measure to check wellness and training adaptation in athletes [22,23], these have not focused on performance improvement based on HRV-guided training but have followed training interventions based on a traditional and nonindividualized methodology.…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Seven studies were included in the quantitative analysis. 15,29,31,3336 The random effects model results revealed that training had small and nonsignificant effect on HRV of competitive soccer players (ES = 0.143, Standard Error (SE) = .108, p = .186, 95% CI [−0.69, 0.355]) and a significant amount of heterogeneity ( Q (26) = 86.758, p < .001, I 2 = 70.032%), as shown in Figure 3.…”
Section: Resultsmentioning
confidence: 98%
“…Most studies measured HRV with a HR monitor, 2931,3436,39 two used a smartphone app plus a HR monitor, 15,32 and one used a smartphone app plus a pulse wave finger sensor. 40…”
Section: Resultsmentioning
confidence: 99%
“…Only one study had a high risk of bias, with a score ≤4 (see Table S1). There were 88 observational studies (i.e., 94%), with 82 prospective cohort studies [41,[43][44][45][46][47][48][49]51,52,[54][55][56][59][60][61][86][87][88]90,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][111][112][113][114][116][117][118][119][120][121][122][123]…”
Section: Characteristics Of the Studies And Risk Of Biasmentioning
confidence: 99%